(untitled) (Clinics, 2021)
OBJECTIVES: Since the outbreak of the novel coronavirus disease 2019 (COVID-19), all health services worldwide underwent profound changes, leading to the suspension of many elective surgeries. This study aimed to evaluate the safety of elective colorectal surgery during the pandemic. METHODS: This was a retrospective, cross-sectional, single-center study. Patients who underwent elective colorectal surgery during the COVID-19 pandemic between March 10 and September 9, 2020, were included. Patient data on sex, age, diagnosis, types of procedures, hospital stay, mortality, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) preoperative screening tests were recorded. RESULTS: A total of 103 colorectal surgical procedures were planned, and 99 were performed. Four surgeries were postponed due to positive preoperative screening for SARS-CoV-2. Surgical procedures were performed for colorectal cancer (n=90) and inflammatory bowel disease (n=9). Laparoscopy was the approach of choice for 43 patients (43.4%), 53 (53.5%) procedures were open, and 3 (3%) procedures were robotic. Five patients developed COVID-19 in the postoperative period, and three of them died in the intensive care unit (n=3/5, 60% mortality). Two other patients died due to surgical complications unrelated to COVID-19 (n=2/94, 2.1% mortality) (po0.01). Hospital stay was longer in patients with SARS-CoV-2 infection than in those without (38.4 versus 10.3 days, respectively, po0.01). Of the 99 patients who received surgical care during the pandemic, 94 were safely discharged (95%). CONCLUSION: Our study demonstrated that elective colorectal surgical procedures may be safely performed during the pandemic; however, preoperative testing should be performed to reduce in-hospital infection rates, since the mortality rate due to SARS-CoV-2 in this setting is particularly high.